2011
DOI: 10.1108/00242531111176826
|View full text |Cite
|
Sign up to set email alerts
|

Exploring reader response to minority ethnic fiction

Abstract: PurposeThe purpose of this paper is to present findings of a study investigating the reading of, and engagement with minority ethnic fiction in UK public libraries, with a particular focus on Black British fiction and Asian fiction in English.Design/methodology/approachA quantitative study of the reading behaviour of a large population of public library users (n=1,047) from the East Midlands region. A survey was distributed at issue points in 16 libraries in nine participating local authorities, to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…This was illustrated to some extent in the findings of a further study by the author (Birdi, 2010;Birdi & Syed, 2011), where a sample population of 1,047 library users contained just 29 (2.8%) readers of Asian fiction in English, 36 (3.4%) readers of Black British fiction and 10 (1%) readers of LGBT fiction.…”
Section: The Contribution Of the Researchmentioning
confidence: 97%
See 2 more Smart Citations
“…This was illustrated to some extent in the findings of a further study by the author (Birdi, 2010;Birdi & Syed, 2011), where a sample population of 1,047 library users contained just 29 (2.8%) readers of Asian fiction in English, 36 (3.4%) readers of Black British fiction and 10 (1%) readers of LGBT fiction.…”
Section: The Contribution Of the Researchmentioning
confidence: 97%
“…Further work is being undertaken by the author to triangulate the findings of this and previous studies based on the same doctoral research (Birdi, 2010;Birdi & Syed, 2011;Birdi, 2011) in order to develop a practical tool both to support the promotion of specific fiction genres, and to provide a stimulus for the readers themselves in selecting their fiction.…”
Section: The Contribution Of the Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Table presents a new, integrative review of the consistencies and differences in demographic and motivational characteristics of the readers of 10 different fiction genres, across the aforementioned studies (Birdi & Syed, ; Birdi, ). Whereas the literature review revealed a lack of clarity as to the identity of the readers of individual fiction genres, emerging from the empirical research is a clearer profile of the more traditional genres (Science Fiction and Fantasy fiction, Romance, Crime, Literary, and War/Spy fiction), and even of the more recently established genres Lad Lit and Chick Lit.…”
Section: Research Findingsmentioning
confidence: 99%
“…Other funding organizations acknowledged include the European Union (Cox, Clough, & Siersdorfer, 2011); the Joint Information Systems Committee of the U.K. higher-education funding councils (Levy, Aiyegabyo, & Little, 2009); the U.K. Museums, Libraries and Archives Council (Wilson & Corrall, 2008); Opening the Book Ltd., a library reader-development consultancy and training company (Birdi & Syed, 2011); PriceWaterhouseCoopers (Polding, Nunes, & Kingston, 2008); and the University's Centre for Health Information Management Research (Brewster & Sen, 2011). While mainstream research funders, such as the Arts & Humanities Research Council, feature prominently here, it is interesting also to note the range of connections with the world of educational and LIS practice.…”
Section: Authorship Of Articles and Dimensions Of Collaborationmentioning
confidence: 99%